2004
DOI: 10.1111/j.1600-079x.2004.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against ionizing radiation‐induced oxidative damage in corpus cavernosum and urinary bladder in rats

Abstract: The objective of this study was to examine the potential radioprotective properties of pharmacological doses of melatonin on corpus cavernosum and bladder tissues of whole-body irradiated (IR) rats. A total of 32 male Sprague-Dawley rats were exposed to irradiation performed with a LINAC which produced 6 MV photons at a focus 100 cm distant from the skin. Under ketamine anesthesia, each rat received a single whole-body dose of 800 cGy. Immediately before and after IR, rats were treated with either saline or me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 26 publications
1
23
0
2
Order By: Relevance
“…The administration of melatonin can prevent or ameliorate chronic inflammation and oxidative damage, fibrosis, necrosis, thrombus, vascular damage, and increased numbers of immune cells in various tissues, such as heart, lung, parotid and submandibular glands, kidneys, spinal cord, the lens, genitourinary system, and others (Karslioğlu et al 2005;Canyilmaz et al 2016;Cakmak Karaer et al 2016;Gürses et al 2014;Haddadi et al 2013;Serin et al 2007;Şener et al 2004;Tahamtan et al 2015). Prevention of pathological damage induced by ionizing radiation using melatonin at different times before and after exposure is a promising outcome.…”
Section: Effect Of Melatonin On Chronic Immune Responses Induced By Imentioning
confidence: 99%
“…The administration of melatonin can prevent or ameliorate chronic inflammation and oxidative damage, fibrosis, necrosis, thrombus, vascular damage, and increased numbers of immune cells in various tissues, such as heart, lung, parotid and submandibular glands, kidneys, spinal cord, the lens, genitourinary system, and others (Karslioğlu et al 2005;Canyilmaz et al 2016;Cakmak Karaer et al 2016;Gürses et al 2014;Haddadi et al 2013;Serin et al 2007;Şener et al 2004;Tahamtan et al 2015). Prevention of pathological damage induced by ionizing radiation using melatonin at different times before and after exposure is a promising outcome.…”
Section: Effect Of Melatonin On Chronic Immune Responses Induced By Imentioning
confidence: 99%
“…Other studies have also shown that melatonin administration can reverse oxidative injury in other tissues and organs, as assessed with biochemical and histopathologic techniques. Thus, melatonin could be useful as a damage-limiting supplement in patients undergoing radiotherapy ( 77,78 ). The mechanisms of action could include inhibition of lipid peroxidation, shown in human fibroblasts ( 79 ), direct radical-scavenging properties, and stimulation of antioxidative enzymes in human skin fibroblasts ( 80 ) and other organ systems ( 16,17 ).…”
Section: Melatonin As Protector Against Skin Damagementioning
confidence: 99%
“…Increased CAT activity is probably related to the inability of the cell to cope with overproduction of H 2 O 2 or *OH (Weiss et al, 2003). Oxidative injury of the colon is accompanied with neutrophil infiltration in both early and later phases after irradiation, whereas contribution of neutrophils to the irradiation injury of the liver occurs at the later phase (Sener et al, 2004). Melatonin-treatment modulated hepatic GST and maintained CAT and MPO activities within the control levels.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently the cellular antioxidant capacity is decreased and the organs become more susceptible to the deleterious effects of ROS (Karbownik and Reiter, 2000). Similarly, total body irradiation in rats has been reported to cause oxidative tissue damage (Sener et al, 2004). The aim of the present study is to investigate the radiation damage mitigating-role of melatonin (delivered after irradiation) against oxidative stress induced liver injury in rats.…”
mentioning
confidence: 98%